Distinct Brain Regions in Physiological and Pathological Brain Aging - Lee, Jin San; Park, Yu Hyun; Park, Seongbeom; Yoon, Uicheul; Choe, Yeongsim; Cheon, Bo Kyoung; Hahn, Alice; Cho, Soo Hyun; Kim, Seung Joo; Kim, Jun Pyo; Jung, Young Hee; Park, Key-Chung; et al. (Frontiers in Aging Neuroscience, 2019)
Background: Studying structural brain aging is important to understand age-related pathologies, as well as to identify the early manifestations of the Alzheimer’s disease (AD) continuum. In this study, we investigated the long-term trajectory of physiological and pathological brain aging in a large number of participants ranging from the 50s to over 80 years of age. Objective: To explore the distinct brain regions that distinguish pathological brain aging from physiological brain aging using sophisticated measurements of cortical thickness. Methods: A total of 2,823 cognitively normal (CN) individuals and 2,675 patients with AD continuum (874 with subjective memory impairments [SMI], 954 with amnestic mild cognitive impairments [aMCI], and 847 with AD dementia) who underwent a high-resolution 3.0-tesla MRI were included in this study. To investigate pathological brain aging, we further classified patients with aMCI and AD according to the severity of cognitive impairment. Cortical thickness was measured using a surface-based method. Multiple linear regression analyses were performed to evaluate age, diagnostic groups, and cortical thickness. Results: Aging extensively affected cortical thickness not only in CN individuals but also in AD continuum patients; however, the precuneus and inferior temporal regions were relatively preserved against age-related cortical thinning. Compared to CN individuals, AD continuum patients including those with SMI showed a decreased cortical thickness in the perisylvian region. However, widespread cortical thinning including the precuneus and inferior temporal regions were found from the late-stage aMCI to the moderate to severe AD. Unlike the other age groups, AD continuum patients aged over 80 years showed prominent cortical thinning in the medial temporal region with relative sparing of the precuneus. Conclusion: Our findings suggested that the precuneus and inferior temporal regions are the key regions in distinguishing between physiological and pathological brain aging. Attempts to differentiate age-related pathology from physiological brain aging at a very early stage would be important in terms of establishing new strategies for preventing accelerated pathological brain aging.